Season of birth as predictor of atopic manifestations. Issue 4 (1st April 1997) - Nilsson, L; Björkstén, B; Hattevig, G; Kjellman, B; Sigurs, N; Kjellman, N-I M
Abstract : The relation between month of birth, sensitisation, and manifestations of atopy was assessed in 209 children who were followed from birth to 12–15 years. Children born during the tree pollen season were less likely to develop allergic rhinoconjunctivitis, IgE antibodies to pollen, or a positive screening test for IgE antibodies (odds ratio 0.28, 0.41, 0.35, respectively) than children born during the rest of the year. The prevalence of IgE antibodies to food and animal dander at 9 months and to atopic disease was higher in children born in the autumn and winter, that is, September to February, compared to the spring and summer (egg 20% v 6%; milk 10% v 2%). Thus sensitisation to pollen and allergic rhinoconjunctivitis is least common in children born in the spring, while birth in September to February is associated with an increased incidence of sensitisation to food and of atopic disease.